Diagnostic accuracy of MR, CT, and ECT in the differentiation of neoplastic from nonneoplastic spine lesions. Issue 5 (7th June 2020) - Liu, Peng; Liang, Yun; Bian, Chong; Wang, Houlei; Jiang, Libo; Hu, Annan; Zhou, Xiaogang; Dong, Jian
Abstract: Aim: To provide guidance for appropriate imaging examinations for diagnosing spinal tumors or tumor‐like lesions. Methods: A total of 121 patients with suspected spinal tumors were included this retrospective study. Each patient underwent ≥2 imaging examinations, including computerized tomography (CT), magnetic resonance (MR), and/or emission computed tomography (ECT). All patients were diagnosed by pathology after core needle or surgical biopsies. The results were compared with those of pathological examinations using paired chi‐squared tests, and compared with each other. Statistical indicators that tested the consistency of the results included McNemar's and kappa coefficients, as well as receiver operating characteristic curves. Results: The differences among MR, CT, ECT, and pathology were not significant. The kappa coefficient of MR, CT, and ECT was 46.1%, 36.0%, and 55.9%, respectively. The area under the curve of ECT, MR, and CT scans was 0.809, 0.705, and 0.704, respectively; and the differences among them were significant ( P < .05). Post hoc multiple comparisons showed no significant differences among imaging examinations in terms of sensitivity, specificity, misdiagnosis rate, and coincidence rate ( P > .05). However, significant differences were noted in the kappa coefficient and missed diagnosis rate ( P < .05). Conclusions: Although ECT was the most accurate imaging method, its high cost and large radiation dosage limit its widespread application. Furthermore, MR verified spinal tumors more effectively; however, CT excluded them more efficiently. In summary, when all factors are considered, MR is still the optimal modality for the diagnosis of spinal tumors, especially during the initial screening.